Estimation of Hemoglobin Level Among the Population of Rajshahi City in Bangladesh - Alam, Muhammad Mahbub ul; Alam, Md Samsul (TAJ: Journal of Teachers Association, 2010)
This study aimed at investigating the hemoglobin level among males and females in Rajshahi City in Bangladesh. The survey was conducted in a perceived healthy population in April 2007. Two hundreds and sixty five males and five hundreds and seventy non-pregnant females aged 10-65 years were purposively selected. Information was obtained on haemoglobin concentration and household socioeconomic status. About 69% of males and 70% of females were found to be anaemic according to WHO anaemia criteria. There was no difference in anaemia prevalence between males and females (p>0.05). Literacy and perceived economic status were associated with anaemia prevalence among females, but not among males. The study suggests that anaemia is highly prevalent in Rajshahi City in Bangladesh which affects both males and females equally. Further studies should be undertaken to confirm the findings and also to examine the causes of anaemia both in males and females in the Rajshahi City of the country to undertake necessary preventive and control measures. TAJ 2010; 23(1): 41-45